Survival of adult patients with acute myeloid leukemia at the Hematology Department at Hospital Pablo Tobón Uribe between 2004 and 2010 - Díaz Correa, Laura María; Madrid Muñoz, Camilo Alberto; Combariza Vallejo, Juan Felipe; Gálvez Cárdenas, Kenny Mauricio; Olaya Colorado, Viviana; Donado Gómez, Jorge Hernando (Medicina UPB, 2012)
Objective: To describe survival of AML patients at Hospital Pablo Tobón Uribe (HPTU) between January 2004 and June 2010. Methods: An observational-descriptive case series in AML patients diagnosed and treated at HPTU between 2004 and 2010. Results: Fifty-three cases of AML, 62.2% women. The median age was 55 years. Median WBC at diagnosis was 9,300. 5 cases (9.43%) were secondary to myelodysplastic syndromes. 51 patients (96.22%) received chemotherapy. The most common treatment regimen was idarubicin plus cytarabine 7x3 in 39 patients (73.58%). 28 patients (52.8%) achieved complete response to induction chemotherapy. 3 patients underwent allogeneic transplantation. 5 patients died during induction, 3 of them over 60 years. The median overall survival was 348 days. The median disease-free survival was 404 days. The overall survival rate at one year was 49%. Conclusions: Series of 53 adult patients with AML. We found similar overall survival times as those reported in previous studies worldwide.